KONSTRUKSI HUKUM PIDANA YANG BERKEMANFAATAN DALAM PENANGANAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - Made Sugi Hartono; Muhamad Jodi Setianto; I Nengah Suastika (Jurnal Komunikasi Hukum, 2023)
This paper is intended to analyze the legal ideals in the form of benefits in handling narcotics abuse. The handling of narcotics abuse has received attention because it is implicated in the overcapacity of the Correctional Institution with its derivative problems. Through the juridical-normative method, this research was carried out using a statutory, case, and conceptual approach. Primary, secondary and tertiary legal materials were collected through literature study. Analysis of the legal materials that have been collected, selected, and systematized is carried out qualitatively and This paper is intended to analyze the legal ideals in the form of benefits in handling narcotics abuse. The handling of narcotics abuse has received attention because it is implicated in the overcapacity of the Correctional Institution with its derivative problems. Through the juridical-normative method, this research was carried out using a statutory, case, and conceptual approach. Primary, secondary and tertiary legal materials were collected through literature study. Analysis of the legal materials that have been collected, selected, and systematized is carried out qualitatively and written in a descriptive-prescriptive manner. The results of the study indicate that the handling of narcotics crimes for abusers leads to punishment. In Buleleng Regency based on court decisions for the last three years from 2019-2021 the average number of abusers shows 29 people. This figure contributes to the overcapacity of prisons which reaches 160%. This phenomenon becomes a reference for judges to make decisions according to the subsidiarity nature of criminal law. Criminal as the ultimum remedium when other means have not been able to solve the problem. Punishment is not sufficient to provide specific or general prevention. Meanwhile, prisons whose main task is to repair and reintegrate social actors are not optimal in carrying out their roles. When reintegration is not optimal, stigmatization appears that degrades the rights of perpetrators to access livelihoods. Benefit occurs when the double track system is criminal and actions can be carried out proportionally based on a strong assessment. Through rehabilitation, the negative impact of sentencing can be avoided and minimize over capacity in prisons.